PERSEPSI KELOMPOK WANITA WAHDAH TERHADAP PROGRAM KB DI WILAYAH ANTANG KOTA MAKASSAR TAHUN 2020 - R, Rahmaniyah; Kurnaesih, Een; Nurlinda, Andi (Patria Artha Journal of Nursing Science, 2021)
Wahdah Muslim groups who live in the Antang area of Makassar City get the target of this research even though the problems found from the Wahdah Muslim group from the results of their interviews with the family planning program argue that family planning is not justified in religions they believe on the grounds of religion through the sunnah of the Prophet Muhammad. that later to get the largest number of people among other members of the community and believe that someone's sustenance has been guaranteed by Allah SWT and that perception is still held firmly by Wahdah women that using family planning is one of the prohibitions and almost all mothers are reluctant to use the family planning program. Research purposes conducted to determine the extent of the Wahdah Women's Group's Perception of the Family Planning Program in the Antang Area of Makassar City. Method:This type of research is a qualitative descriptive study with 10 informants using purposive sampling technique taken from various different aspects such as the type of occupation, education level, age, marital status, and the amount of parity. Results: The results showed that the perception of the Wahdah women's group regarding the family planning program in the Antang area, Makassar City in terms of Islamic, cultural, social, contraceptive, economic, and marriage perspectives were related to the family planning program